65 Improving Medicines Safety for Care Homes Residents. (6th February 2020) - Okoli, U; Kent, J; Gadhia, S
Abstract: Introduction: Care home residents often have multiple, chronic conditions and are receiving complex treatment regimes, yet 30–50% of prescribed medicines are not taken as recommended [1]. Polypharmacy and medication errors are common. Evidence suggests that there is a linear increase in medication errors with the number of medications a patient is prescribed. This paper describes an approach to identity and address inappropriate polypharmacy and safety concerns in Buckinghamshire care homes. The workforce used was: primary care and care home pharmacists, technicians and geriatricians. Methods: A successful business proposal enabled a new interdisciplinary model of care to be established. This was delivered in 2768 Buckinghamshire care home beds (63% of Bucks ICS bed capacity). The CCG pharmacists, GPs and pharmacy technicians reviewed medication for all residents followed by a medication and clinical review by a geriatrician for the most complex individuals. Other community specialist teams were included as part of a Multidisciplinary team as needed. Data on reviews, medicines stopped and safety were collected from 2013–2018. Results: Overall 2134 medications were stopped for 1268 residents of 2102 reviewed, with 505 interventions to reduce falls risk. 942 safety issues were identified and resolved. Total savings on medicines optimisation, waste and non-elective admission prevented was £619, 000. System wide safety included: community psychiatric nurse to support dementia diagnosis, specialist enteral feeding nurse reinstated and a new website to share and disseminate good practice standards. Conclusions: Future direction of this work focuses on system wide improvements to promote multi-organisational interdisciplinary healthcare and social services professionals work in care homes. NHSE Pharmacy integrated funding has provided extra pharmacists and technicians to support the 37% of the care home beds not yet covered by March 2020. Reference: 1. Horne R, Weinman J, Elliot R, et al. 2005, NHS National Coordinating Centre for service delivery and organisation report.